Phytochemical Profiling of Leaf, Stem, and Tuber Parts of Solena amplexicaulis (Lam.) Gandhi Using GC-MS - Krishnamoorthy, Karthika (Int Sch Res Notices, 2014)
Objective. To explore the possible bioactive compounds in the methanolic extracts of leaf, stem, and tuber parts of the medicinal climber, Solena amplexicaulis, using GC-MS. Methods. GC-MS analysis of the plant extracts were performed by using GC-MS-5975C [Agilent] and mass spectra of the compounds found in the extract was matched with the data in the library of National Institute of Standards and Technology (NIST). Results. Thirty-five compounds were determined to be present in the parts studied. The active principles with their retention time, molecular formula, molecular weight, peak area, structure, category of the compounds, and activities were predicted. The most prevailing compounds were phytol (38.24%) in leaf, 4-(4-ethoxyphenyl) but-3-en-2-one (56.90%) in stem, and 9,17-octadecadienal, (Z)- (21.77%) in tuber. Conclusion. This study revealed that the species S. amplexicaulis is a good source of many bioactive compounds like terpenes, triazines, esters, alkanes, alcohols, hydrocarbons, aldehydes, amides, and so forth. That justifies the traditional usage of this species.